How Does Corporate Social Responsibility Affect Sustainability of Social Enterprises in Korea? - Qing, Chenglin; Jin, Shanyue (Frontiers in Psychology, 2022)
Social enterprises (SEs) are a new concept, integrating corporate profitability and social purposes. SEs seek to realize sustainable social values, rather than short-term profits. It is therefore important to study the factors that affect the sustainable management of SEs. Corporate social responsibility (CSR) is known to improve corporate image and performance; it can also promote the sustainable development of companies. Innovation has been described as the driving force behind corporate growth and ultimate performance. This study aims to investigate whether CSR can affect sustainability through the economic and social performance of SEs. In addition, it attempts to verify the moderating role of innovativeness in the relationship between CSR and social enterprise (SE) performance. Using survey data from 226 employees of 204 SEs in Korea, we have empirically tested this conceptual framework. The results suggest that, while CSR can improve sustainability through economic and social performance, innovativeness has no moderating effect on the relationship between CSR and SE performance. This study enriches our understanding of the important role played by CSR in driving SE sustainability. It provides new insights into the mechanisms through which SEs can achieve sustainable development. It also contributes to the literature by emphasizing the need for innovation through technical support for SEs.